Osmotic potentials on water uptake and germination of Guazuma ulmifolia Lam. (Sterculiaceae) seeds - Braga, João Filgueiras; Delachiave, Maria Elena Aparecida [UNESP]; Pinho, Sheila Zambello de [UNESP]; Braga, Lúcia Filgueiras; Souza, Marcilio Pereira (My University, 2010)
Osmotic potentials on water uptake and germination of Guazuma Ulmifolia Lam. (Sterculiaceae) seeds. This work was carried out in the Germination Lab. of the Department of Botany, Institute of Biosciences, São Paulo State University (UNESP), Botucatu, São Paulo State, Brazil. The aims of this work were to determine the water uptake curve and to evaluate the germination of Guazuma ulmifolia seeds subjected to different water potentials. For the water uptake curve, seven replicates of 50 pre-scarified seeds were placed onto paper moistened with 15 mL PEG 6000 solution under the potentials 0 (control), -0.3 and -0.6 MPa at 25o C in the darkness. For the germination assay, four replicates of 50 seeds were subjected to the same above-described conditions; however, one lot of seeds was modified when there was variation in the refractometric index, whereas the remaining ones were kept in the same solutions until the end of the experiment. All three phases of water uptake were detected under 0 and -0.3 MPa; however, phase II was prolonged under -0.6 MPa and germination was not observed. For 0 and -0.3 MPa, the adopted statistical models consisted of asymptotic (phases I and II) and exponential (phase III) functions, y = a*[1 - b*exp (-c*t) + exp (-d + e*(t - t0)]. For -0.6MPa, only the asymptotic function y = a* [1 - b* exp (-c*t)] was used since there was no evidence of germination. The germination final percentage and speed index were lower under -0.3 MPa, mainly when solutions were not replaced; besides, germination was not detected under -0.6 MPa, with or without solution replacement.
Keywords: Model; Imbibition; Forest seed; Water stress